Analysis of Gut Microbiota as a Diagnostic Biomarker for Lung Adenocarcinoma with Qi-Deficiency and Phlegm-Turbid Stagnation - Chen, Jiabin; Hu, Qinqin; Chai, Kequn; Wang, Sheng (Combinatorial Chemistry & High Throughput Screening, 2025)
Background In Lung Adenocarcinoma (LUAD), Qi-deficiency and Phlegm-turbid stagnation (QP) are the most prevalent Traditional Chinese Medicine (TCM) syndrome. Methods Herein, we collected 90 fecal samples (Healthy individual (H): 30; other syndrome (O): 30; QP: 30) and explored the composition and diversity of gut microbiota in LUAD patients with QP syndrome using 16s-rRNA sequencing. Then, we identified biomarkers for QP syndrome in LUAD patients with Linear Discriminant Analysis (LDA) effect size (LEfSe) and applied logistic regression analysis to construct a diagnostic model evaluated with the area under the receiver operating characteristic curve (AUC) and validated with data from metagenomics. Results The α diversity and β diversity revealed that the microbiota community structure in LUAD patients with QP syndrome was different from that with healthy individuals and LUAD patients with other syndromes. At the phylum level, the QP group had more abundance of Bacteroidetes and less Proteobacteria than the O group. At the genus level, the abundance of 4 genera (Bacteroides, Parabacteroides, Prevotella, and Flavonifractor) was different between the QP group and O group. Moreover, LEfSe indicated that those 4 genera might be the biomarkers for LUAD patients with QP syndrome. Then, we used those 4 genera to develop a diagnostic model. The AUC based on 16s-rRNA sequencing and metagenomics was 0.989 and 1, respectively. Conclusion A diagnostic model was developed, which would be an available tool for the clinical diagnosis of LUAD with QP syndrome.
Keywords: diagnostic model